Carbohydrate intake in young female cross-country skiers is lower than recommended and affects competition performance - Kettunen, O.; Mikkonen, R.; Mursu, J.; Linnamo, V.; Ihalainen, J. K. (Frontiers in Sports and Active Living, 2023)
Purpose: (1) To evaluate if energy availability (EA), macronutrient intake and body composition change over four training periods in young, highly trained, female cross-country skiers, and (2) to clarify if EA, macronutrient intake, body composition, and competition performance are associated with each other in this cohort.